Strategi Meningkatkan Kemampuan Membaca Pemahaman Melalui Metode SQ3R di MIS Al Hikmah Masangan Bungah Gresik - Assyifa’ , Siti Nur; Sularti, Siti; Solihati, Solihati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of implementing the SQ3R (Survey, Question, Read, Recite, Review) method in improving students’ reading comprehension skills at MIS Al Hikmah Masangan Bungah Gresik. This research adopts a Classroom Action Research (CAR) approach conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 28 fifth-grade students. Data were collected through reading comprehension tests, observations, and documentation. The results showed that the SQ3R method significantly improved students’ reading comprehension skills. In the first cycle, the average student comprehension score was 66, while in the second cycle, it increased to 83. This improvement indicates that the SQ3R method helps students understand texts more systematically and effectively. Therefore, the SQ3R method is recommended as a learning strategy to enhance students’ reading comprehension skills at the elementary school level.